The impact of cancer on the risk of death with a functioning graft of Italian kidney transplant recipients. Issue 2 (15th September 2021) - Taborelli, Martina; Serraino, Diego; Cimaglia, Claudia; Furian, Lucrezia; Biancone, Luigi; Busnach, Ghil; Todeschini, Paola; Bossini, Nicola; Iaria, Maurizio; Campise, Maria R.; Veroux, Massimiliano; Citterio, Franco; et al.
Abstract : This study assessed the impact of cancer on the risk of death with a functioning graft of kidney transplant (KT) recipients, as compared to corresponding recipients without cancer. A matched cohort study was conducted using data from a cohort of 13 245 individuals who had undergone KT in 17 Italian centers (1997–2017). Cases were defined as subjects diagnosed with any cancer after KT. For each case, two controls matched by gender, age, and year at KT were randomly selected from cohort members who were cancer‐free at the time of diagnosis of the index case. Overall, 292 (20.5%) deaths with a functioning graft were recorded among 1425 cases and 238 (8.4%) among 2850 controls. KT recipients with cancer had a greater risk of death with a functioning graft (hazard ratio, HR = 3.31) than their respective controls. This pattern was consistent over a broad range of cancer types, including non‐Hodgkin lymphoma (HR = 33.09), lung (HR = 20.51), breast (HR = 8.80), colon‐rectum (HR = 3.51), and kidney (HR = 2.38). The survival gap was observed throughout the entire follow‐up period, though the effect was more marked within 1 year from cancer diagnosis. These results call for close posttransplant surveillance to detect cancers at earlier stages when treatments are more effective in improving survival. Abstract : Kidney transplant recipients with cancer, compared to a matched cohort of cancer‐free recipients, show a 3‐fold higher risk of death with a functioning graft.